Analysis of Paediatric Liaison Service Caseload Trends at King’s College Hospital CAMHS From November 2018 to December 2024: Impact of COVID-19 and Post-Pandemic Recovery - Khalid Magzoub; Idura Hisham; Sulagna Chakrabarti (BJPsych Open)
Aims: To analyse the in-hours emergency/crisis caseload trends of the King’s College Hospital (KCH) CAMHS Paediatric Liaison Service from November 2018 to December 2024, focusing on the impact of the COVID-19 pandemic and the subsequent recovery. The study aims to identify patterns in service demand and contextualise these trends with key pandemic milestones.